(untitled) (Journal of Society of Surgeons of Nepal, 2018)
Introduction: Displaced acetabular fracture is a consequence of high energy trauma and commonly seen in young population. There has been increasing trend towards operative management of these injuries to provide early mobilisation and prevent complication of incongruent reduction. Methods: A retrospective analysis on clinical outcome of operative management of 16 displaced acetabular fracture using Merle d’Aubigne hip score carried out at university teaching hospital carried out between 2015 to 2017 AD Result: The Merle d’Aubigné hip score at final follow of 3 to 30 months period ranged from 7 to 17. The average score was 13.8. Very good result was seen in 68.75%, fair result in 12.5%. Conclusion: Operative management of displaced acetabular fracture gives excellent to good short term outcome in most of the cases.